Avaliação do nível de higiene oral e condição periodontal de escolares de 15 a 19 anos da rede pública de Campina Grande, Paraíba - Santos, Fabio Gomes dos (2013)
Periodontal diseases are considered a public health problem in the world, affecting people in all ages, including adolescents. The aim of this study was to evaluate the oral hygiene level and periodontal status of 15-19 years-old schoolchildren in the city of Campina Grande, Brazil. A cross-sectional study was carried out among 630 students enrolled at public schools, randomly selected by cluster sampling design. For data collection, a form containing socioeconomic variables and those related to oral hygiene was used. Periodontal status was assessed by applying the Simplified Oral Hygiene Index (OHI-S) and the Community Periodontal Index (CPI).Two calibrated examiners (kappa>0.61) performed the clinical examinations. Data were descriptively and inferentially analyzed using the chi-square test, adopting significance level of 5%.There was no statistically significant difference between socioeconomic aspects and periodontal status (p>0.05). All students reported use the toothbrush and toothpaste, while interdental cleaning with dental floss was reported by only 44.1%. The use of dental floss was higher between females (p<0.027). Most of individuals (59.7%) had satisfactory oral hygiene status (OHI-S<1.1), but only 1.3% had healthy periodontium (CPI=0). The prevalence of calculus, bleeding on probe and shallow pockets (4-5mm) were 37.8%, 34.4% and 24.3% respectively. It was concluded that the 15-19 years-old schoolchildren have healthy oral hygiene habits, but showed a high prevalence of bleeding, calculus and shallow periodontal pocket.